COMMUNITY EMPOWERMENT THROUGH VILLAGE-OWNED ENTERPRISES "ENGGAL MAKMUR" MOJOWARNO VILLAGE MOJOWARNO DISTRICT JOMBANG REGENCY - Madania Uki Anindita; Tukiman Tukiman (DIA: Jurnal Administrasi Publik, 2022)
Community Empowerment in Mojowarno Village, Mojowarno District, Jombang Regency through Village Owned Enterprises (BUM Desa) is currently in the spotlight. BUM Desa "Enggal Makmur" Mojowarno Village was awarded 1st Place in the BUMDES Award 2020 event in the field of social media and digital marketing because it succeeded in creating a website innovation in the form of a marketplace to help the efforts of the Mojowarno Village community so that it is hoped that the village community can be more empowered. This study aims to determine how the process of community empowerment through BUM Desa "Enggal Makmur" Mojowarno Village, Mojowarno District, Jombang Regency. Community empowerment through BUM Desa "Enggal Makmur" Mojowarno Village is seen using 6 goals to achieve community empowerment, better institution, better business, better income, better environment, better living, and better community. This type of research is qualitative research. The results of this study indicate that the Mojowarno Village community has not been fully empowered through the BUM Desa "Enggal Makmur" because of the 6 indicators for achieving community empowerment goals, only 2 indicators can be implemented by Enggal Makmur Village BUM in the process of empowering the Mojowarno Village community.